Comparative Study of Sustainable Water Pollution Management in Godavari River in Nashik City - Ashutosh Tombare; Prajwal Ghodekar; 3Mohan Dhobale; Lubhan Patil; V E Kothawade (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The Godavari River in Nashik City faces severe water pollution due to industrial, agricultural, and domestic activities. This study aims to find sustainable solutions to manage water pollution in the river. We collected water samples, analyzed data, and consulted with stakeholders to understand the pollution sources and impacts. Our study recommends sustainable practices, such as wastewater treatment, efficient irrigation systems, and community-led initiatives. Implementing these solutions can improve water quality, protect public health, and preserve the river’s ecosystem. This research contributes to the development of effective water pollution management strategies for the Godavari River and similar rivers worldwide.